Characterization of $M_{11}$ and $L_3(3)$ by their commuting graphs - Salarian, M. R. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
For the groups $M_{11}$ and $L_3(3)$, we show that their commuting graphs are unique.